Optimasi Kinerja Fuel Gas Booster Compressor (K-750X B) dalam Menyediakan Bahan Bakar Bertekanan Tinggi di Unit 75 PT. X dengan Simulasi Hysys - Nurraiyan, Nurraiyan; Sami, Muhammad; Elfiana, Elfiana (Jurnal Teknologi, 2025)
Fuel Gas Booster Compressors play a critical role in process industries by increasing the pressure of fuel gas from low to high levels to meet operational requirements. This study aims to optimize the performance of the Fuel Gas Booster Compressor (K-750X B) at Unit 75 PT. X using Aspen HYSYS simulation. Optimization is conducted by analyzing the effects of operational parameters, including flow rate, pressure, and feed gas temperature from the dehydration unit, on compressor performance. The research methodology involves collecting actual operational data from the Distributed Control System (DCS) and field measurements, simulating the process using Aspen HYSYS, and validating simulation results with real operational data. The simulation results indicate significant discrepancies between actual and theoretical operating conditions, particularly in terms of flow rate, pressure, and temperature. The actual flow rate was found to be 2.125 m³/s, significantly lower than the theoretical 5.616 m³/s. Additionally, the feed suction and discharge temperature and pressure exhibited declines, impacting the compressor’s efficiency. This study confirms that simulation-based optimization provides valuable insights into improving the operational efficiency of Fuel Gas Booster Compressors